Ketamine administration reduces amygdalo‐hippocampal reactivity to emotional stimulation - Scheidegger, Milan (Hum Brain Mapp, 2016)
Increased amygdala reactivity might lead to negative bias during emotional processing that can be reversed by antidepressant drug treatment. However, little is known on how N‐methyl‐d‐aspartate (NMDA) receptor antagonism with ketamine as a novel antidepressant drug target might modulate amygdala reactivity to emotional stimulation. Using functional magnetic resonance imaging (fMRI) and resting‐state fMRI (rsfMRI), we assessed amygdalo‐hippocampal reactivity at baseline and during pharmacological stimulation with ketamine (intravenous bolus of 0.12 mg/kg, followed by a continuous infusion of 0.25 mg/kg/h) in 23 healthy subjects that were presented with stimuli from the International Affective Picture System (IAPS). We found that ketamine reduced neural reactivity in the bilateral amygdalo‐hippocampal complex during emotional stimulation. Reduced amygdala reactivity to negative pictures was correlated to resting‐state connectivity to the pregenual anterior cingulate cortex. Interestingly, subjects experienced intensity of psychedelic alterations of consciousness during ketamine infusion predicted the reduction in neural responsivity to negative but not to positive or neutral stimuli. Our findings suggest that the pharmacological modulation of glutamate‐responsive cerebral circuits, which is associated with a shift in emotional bias and a reduction of amygdalo‐hippocampal reactivity to emotional stimuli, represents an early biomechanism to restore parts of the disrupted neurobehavioral homeostasis in MDD patients. Hum Brain Mapp 37:1941–1952, 2016. © 2016 Wiley Periodicals, Inc.